HUBUNGAN ANTARA MOTIVASI, BEBAN KERJA, DAN LINGKUNGAN KERJA DENGAN KELELAHAN KERJA - Bintang Mareeta Dewi (Universitas Airlangga, 2018)
Cooperative is a form of business entity that develope steadily and manages different businesses includingindustrial sector. Koperasi KAREB is a cooperative engaged in different sector such as industrial sector in the form of Processing Units engaged in the tobacco processing. The development of industrial sector made Cooperative KAREB exert machines and manpower in the production process to achieve maximum output. The utilization of manpower can cause the onset of fatigue. Work fatigue becomes the basic complaint to be felt by every labor and can be caused by many different factors. The purpose of this research is to analyze the relationship between motivation, workload, and work environment with fatigue in the Unit Processing Koperasi KAREB. This research is an observational analytic research with cross sectional design. The population of this research is labors in Unit Processing Koperasi KAREB as many as 46 labors with the sample of 35 people that are taken using simple random sampling method. Data retrieval technique used questionnaires. Data analysis technique used Spearman Correlation. The results showed that 28.6% workers suffered mild fatigue, 65.7% workers suffered average fatigue, and 5.7% workers suffered severe fatigue. Statistical tests indicate that there is a relationship between motivation (p = 0.004), workload (p = 0.031), and temperature perception (p = 0.042) with fatigue. While, there is no relationship between noise and fatigue. It can be conclude that fatigue is influenced by some factors such as motivation, workload, and temperature of the working environment. Keywords: fatigue, motivation, noise, temperature,workload.